Role of Transcranial Ultrasound for Hypoxic Ischemic Insult Keeping MRI as a Gold Standard - Anayatullah, Maryam; Dogar, Iqbal Hussain; Ahmad, Mian Waheed; Gahffar, Sidra (Indus Journal of Bioscience Research, 2025)
Background: Hypoxic-ischemic insult is an important cerebral pathology in neonates, which is caused by reduced oxygen and blood flow during parturition. Early diagnosis of hypoxic-ischemic insult in neonates is important to prevent sequelae. Magnetic resonance imaging is considered an effective diagnostic tool; however, it is not easily accessible and is quite expensive. Objective: To determine the diagnostic accuracy of transcranial ultrasound in detecting hypoxic ischemic encephalopathy taking MRI as gold standard. Study Design: Cross sectional validation study. Duration and Place of Study: This study was conducted from 2 January 2025 to 2 May 2025 in Department of Radiology, Gujranwala Teaching Hospital Gujranwala. Methodology: A total of 156 newborns with birth asphyxia and gestational age more than 32 weeks were included. Transcranial ultrasound was performed using high frequency probe through anterior fontanelle. Magnetic resonance imaging was done on 1.5 tesla machine. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were calculated by 2×2 contingency table. Results: Mean gestational age was 36.87±1.99 weeks and mean birth weight was 2.66±0.51 kg. Sensitivity was 85.5%, specificity 70.3%, diagnostic accuracy 75.6%, positive predictive value 61% and negative predictive value 89.9%. Conclusion: Transcranial ultrasound is useful screening tool with good sensitivity and high negative predictive value for detecting hypoxic ischemic insult in neonates.